1992
DOI: 10.1007/bf00304791
|View full text |Cite
|
Sign up to set email alerts
|

Management of brain abscess in children: review of 130 cases over a period of 21 years

Abstract: The data on 130 children with brain abscesses treated over 21 years (1970-1990) were analyzed retrospectively. The whole group included four infants. Chronic ear infection and cyanotic congenital heart disease were the most common predisposing factors. In infants, meningitis and/or ventriculitis were dominant in the etiopathogenesis. Cases were evaluated according to the treatment received and also according to time periods. More than half of the patients (n = 74) in this series were treated by primary or seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 20 publications
0
47
0
5
Order By: Relevance
“…The rate of mortality reduced considerably when compared with the pre-CT period. 36 Tekkok and Erbengi 39 found a reduction in mortality rate from 30% in the era before the use of CT to 6% in the last 5 years and 0% in the last 3 years of their study. Unenhanced CT of an encapsulated abscess reveals a thin ring outlined by the central area of necrosis and peripheral edema; in scans obtained after the administration of a contrast agent, this ring shows strong enhancement.…”
Section: Imaging Studiesmentioning
confidence: 94%
See 3 more Smart Citations
“…The rate of mortality reduced considerably when compared with the pre-CT period. 36 Tekkok and Erbengi 39 found a reduction in mortality rate from 30% in the era before the use of CT to 6% in the last 5 years and 0% in the last 3 years of their study. Unenhanced CT of an encapsulated abscess reveals a thin ring outlined by the central area of necrosis and peripheral edema; in scans obtained after the administration of a contrast agent, this ring shows strong enhancement.…”
Section: Imaging Studiesmentioning
confidence: 94%
“…26,40,44 In the pediatric patient group, the most common predisposing factor is congenital heart disease or adjacent cranial infection. 1,2,12,39 Recently, Auvichayapat et al 2 in their series of 107 cases involving infants and children, found chronic otitis media the second most common predisposing factor after congenital heart disease, and they concluded that this was probably due to the poor socioeconomic status leading to neglect of chronic otitis media, with children going without treatment for years. Brain abscesses in patients with immunosuppression 12,40,44 and postneurosurgical nosocomial bacterial brain abscesses 45 are also increasing in incidence.…”
Section: Pathogenesis and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…7,9,10,12,14,16 Improved imaging techniques combined with improved culturing techniques and advances in surgical and medical management of brain abscesses have contributed to the reduction in the mortality rate, which has been seen over the last century. 9,25 However, this condition remains life threatening, especially in children who are immunocompromised, who are Ͻ 1 year old, who present with significant surgery-related neurological deficits, in whom the initial diagnosis was delayed, the abscess has ruptured into the ventricle, or surgical management was complicated by hemorrhage.…”
Section: Outcomementioning
confidence: 99%